Clinical indicators to monitor health care in low back pain: a scoping review - Dos Santos, Vanessa L.; Sato, Karen S.; Maher, Chris G.; Vidal, Rubens V.C.; Grande, Guilherme H.D. [UNESP]; Costa, Leonardo O.P.; Machado, Gustavo C.; Ferreira, Giovanni E.; Buchbinder, Rachelle; Oliveira, Crystian B. [UNESP] (Oxford University Press (OUP), 2024)
Clinical care indicators for low back pain can be used to monitor healthcare practices and consequently be used to evaluate success of strategies to improve care quality. The aim of this study was to identify the clinical care indicators that have been used to measure appropriateness of health care for patients with low back pain. We conducted a systematic search of five electronic databases and Google to identify clinical care indicators that have been used to measure any aspect of care for people with low back pain. Care indicators were narratively described according to their type (i.e. structure, process, or outcomes) and categorized by their purpose (e.g. to measure aspects related to assessment, imaging requests, treatment/prevention, and outcomes). A total of 3562 and 2180 records were retrieved from electronic databases and Google searches, respectively. We identified 280 indicators related to low back pain care from 40 documents and publications. Most quality indicators were process indicators (n = 213, 76%), followed by structure (n = 41, 15%) and outcome indicators (n = 26, 9%). The most common indicators were related to imaging requests (n = 41, 15%), referral to healthcare providers (n = 30, 11%), and shared decision-making (n = 21, 7%). Our review identified a range of clinical care indicators that have been used to measure the quality of health care for people with low back pain. Our findings will support a Delphi study to reach international consensus on what would be the most important and feasible indicators for a minimum dataset to be collected globally.
Keywords: clinical indicators; healthcare quality monitoring; low back pain; public health